Relationship between maceration and wound healing on diabetic foot ulcers in Indonesia: a prospective study. Issue 3 (10th July 2016) - Haryanto, Haryanto; Arisandi, Defa; Suriadi, Suriadi; Imran, Imran; Ogai, Kazuhiro; Sanada, Hiromi; Okuwa, Mayumi; Sugama, Junko
Abstract: The aim of this study was to clarify the relationship between maceration and wound healing. A prospective longitudinal design was used in this study. The wound condition determined the type of dressings used and the dressing change frequency. A total of 62 participants with diabetic foot ulcers (70 wounds) were divided into two groups: non‐macerated ( n  = 52) and macerated wounds ( n  = 18). Each group was evaluated weekly using the Bates–Jensen Wound Assessment Tool, with follow‐ups until week 4. The Mann–Whitney U test showed that the changes in the wound area in week 1 were faster in the non‐macerated group than the macerated group ( P  = 0·02). The Pearson correlation analysis showed a moderate correlation between maceration and wound healing from enrolment until week 4 ( P  = 0·002). After week 4, the Kaplan–Meier analysis showed that the non‐macerated wounds healed significantly faster than the macerated wounds (log‐rank test = 19·378, P  = 0·000). The Cox regression analysis confirmed that maceration was a significant and independent predictor of wound healing in this study (adjusted hazard ratio, 0·324; 95% CI, 0·131–0·799; P  = 0·014). The results of this study demonstrated that there is a relationship between maceration and wound healing. Changes in the wound area can help predict the healing of wounds with maceration in clinical settings.